Geographical Survey of Air Pollution of Patna Urban Town - KUMAR, ANUJ (Asian Journal of Chemistry, 2010)
Interannual variation of air pollutions in Patna urban have been analyzed from different places and the two primary pollutants SO2, NO2 and suspended particulate matter. The methodology involves obtaining the ambient quality data for the study period April 1997 to March 2001.